Implementation of Sensitive Data Encryption and Access Management in Stream Mobile Application for Loan Submission (Case Study: PT. Intikom Berlian Mustika) - Rizky Adyatma; Hafni; Muhammad Zen (Cattleya Darmaya Fortuna, 2026)
The increasing digitalization of human resource management systems has led to the development of mobile applications that handle sensitive employee data, including financial information related to loan submissions. PT. Intikom Berlian Mustika's Stream Mobile application serves as an Employee Self-Service (ESS) platform that enables employees to submit loan requests directly through their mobile devices. However, this convenience introduces significant security challenges, particularly concerning the protection of sensitive personal and financial data. This study focuses on designing and implementing robust data encryption mechanisms and access management controls within the Stream Mobile application to safeguard employee information during the loan submission process. The research employs a qualitative approach combined with system development methodology, utilizing AES-256 encryption for data at rest and TLS 1.3 for data in transit, alongside Role-Based Access Control (RBAC) and OAuth 2.0 authentication. The implementation was evaluated through security testing, including penetration testing and vulnerability assessments. Results demonstrate that the implemented security measures significantly enhance data protection, with encryption reducing unauthorized access risks by 98.5% and access management preventing privilege escalation attempts. The system successfully maintains compliance with Indonesian Personal Data Protection regulations while ensuring seamless user experience. Key features—including multi-layer encryption, granular access controls, and comprehensive audit logging—contribute to establishing a secure environment for sensitive loan transaction data. This research provides practical insights for organizations implementing mobile HRIS systems with financial transaction capabilities, emphasizing the critical balance between security and usability.